2012
DOI: 10.1002/jssc.201200439
|View full text |Cite
|
Sign up to set email alerts
|

A novel microextraction by packed sorbent–gas chromatography procedure for the simultaneous analysis of antiepileptic drugs in human plasma and urine

Abstract: A simple, accurate, and sensitive microextraction by packed sorbent-gas chromatography-mass spectrometry method has been developed for the simultaneous quantification of four antiepileptic drugs; oxcarbazepine, carbamazepine, phenytoin, and alprazolam in human plasma and urine as a tool for drug monitoring. Caffeine was used as internal standards for the electron ionization mode. An original pretreatment procedure on biological samples, based on microextraction in packed syringe using C(18) as packing materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…This has prompted us to investigate the applicability of monitoring all three AEDs using only one DBS. Considering the volatile nature of VPA and previous success in quantitation of CBZ and PHT using gas chromatography mass spectrometry (GCMS) [16], GCMS was ultimately chosen as the analytical tool for simultaneous determination of these AEDs. This study was conducted with the main objective of comparing the newly developed GCMS assay with the conventional immunoturbimetric assays.…”
Section: Introductionmentioning
confidence: 99%
“…This has prompted us to investigate the applicability of monitoring all three AEDs using only one DBS. Considering the volatile nature of VPA and previous success in quantitation of CBZ and PHT using gas chromatography mass spectrometry (GCMS) [16], GCMS was ultimately chosen as the analytical tool for simultaneous determination of these AEDs. This study was conducted with the main objective of comparing the newly developed GCMS assay with the conventional immunoturbimetric assays.…”
Section: Introductionmentioning
confidence: 99%
“…This optimization is usually based on the determination of these drugs, which are included in the regimen, in plasma samples for TDM purposes. For these purposes, GC or LC methods are commonly used for the simultaneous determination of different antiepileptic drugs . To our knowledge, the developed method is the first validated GC–MS method for the determination of lacosamide in human plasma.…”
Section: Resultsmentioning
confidence: 99%
“…In the pretreatment step of biological samples, the previous studies have used mainly LLE or direct injection after protein precipitation . The direct injected samples after protein precipitation are mainly used for LC analysis and they usually show high matrix effect and significant signal suppression . The development of a sufficient extraction procedure of lacosamide from human plasma was considered necessary for a reliable GC–MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Methanol can readily permeate the silane sorbent that is enriched with analyte from the aqueous eluate. In studies describing the determination of drugs in plasma and urine by MEPS-GC, methanol showed better elution efficiency than other organic solvents [30,31].…”
Section: Positive Control Analysismentioning
confidence: 98%